2019
DOI: 10.1186/s12935-019-1001-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel cell glycolysis related gene signature predicting survival in patients with endometrial cancer

Abstract: BackgroundEndometrial cancer (EC) is one of the three major gynecological malignancies. Numerous biomarkers that may be associated with survival and prognosis have been identified through database mining in previous studies. However, the predictive ability of single-gene biomarkers is not sufficiently specific. Genetic signatures may be an improved option for prediction. This study aimed to explore data from The Cancer Genome Atlas (TCGA) to identify a new genetic signature for predicting the prognosis of EC.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…Several research studies have focused on the systematic analysis of glycolysis and tumors, including glioblastoma (15), liver cancer (16), and endometrial cancer (17). However, comprehensive analysis of the interrelation between glycolysis, immune infiltration, and clinical prognosis in GC patients is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have focused on the systematic analysis of glycolysis and tumors, including glioblastoma (15), liver cancer (16), and endometrial cancer (17). However, comprehensive analysis of the interrelation between glycolysis, immune infiltration, and clinical prognosis in GC patients is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A three-gene glycolytic signature (MET, B3GNT3 and SPAG4) can act as an independent factor for generating a prognosis for patients with pancreatic ductal adenocarcinoma [22]. A nine-gene signature associated with cellular glycolysis was a potent indicator for the prediction of overall survival in patients with endometrial cancer [23]. The glycolysis score represented by expression of ten glycolytic genes predicted unfavorable clinical outcome for patients with glioblastoma and was closely related to mesenchymal subtype and mutation of IDH1 in glioblastoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…breast cancer and leukaemia. [22][23][24][25][26][27][28] On the other hand, B4GALT1 is frequently methylated or down-regulated in colorectal cancer and endometrial cancer 29,30 and can be used to predict patient outcomes. In this study, based on the analysis of TCGA database, we Taken together, this study identified AKR1C3 as a new critical regulator that increases the expression and transcriptional activity of AR-V7 by forming a complex to inhibit its protein degradation.…”
Section: The Ar-v7/akr1c3 Complex Represses the Transcription Of B4mentioning
confidence: 99%